Distinctive analysis of fluid flow behavior of AC electroosmotic micropump - Abhari, Farideh (2013)
The fluid flow behavior in an alternating current (AC) electroosmotic micropumping device has been studied experimentally and theoretically using an electrohydrodynamic theoretical model applied to a computer simulation model. It has been analyzed using two different theoretical approaches; first is "Ramos slip velocity" and the second, "Coupled ACEO numerical" model. This micropump is using a coplanar microelectrode array that engages the principle of AC electroosmosis (EO), ion driven in the direction of surfaces due to Coulomb forces by tangential electric fields. These ions, when activated, produce a net movement of fluid flows caused by viscous drag forces. The result of AC electric field to an electrolyte using coplanar microelectrodes creating a travelling wave of potential and has given steady fluid flow across the microelectrode array. The flow has its origin in the interaction of the tangential component of the nonuniform field with the induced charge in the electrical double layer on the electrode surfaces. The velocity that experimentally measured was from movies collected by researcher at Southampton University in United Kingdom. Two micrometer size of particles were suspended in potassium chloride (KCl) with conductivity 14.5 µS/m was used as an aid of visualization in order to measure the fluid velocity when the device work as pump. The experimental results were reviewed for different range of voltages (2 Vpp- 20 Vpp) and frequencies (10 kHz -10 MHz). Maximum velocity was achieved at an AC signal frequency of 90 kHz in 16 Vpp approximately 3.1 x 10-1 µm/s. They were in good agreement with the theoretical predictions, produced using the computer simulation model with MATLAB and COMSOL. Overall, the bulk fluid flow driven by this surface is numerically calculated as a function of voltage and frequency. It shows a good agreement between the numerical and experimental streamline and comparable to previously computer simulation framework to analyze future micropump design concepts.